A Chinese Medicine Formula Gegen Qinlian Decoction Suppresses Expansion of Human Renal Carcinoma With Inhibition of Matrix Metalloproteinase-2. (January 2015) - Wang, Ning; Feng, Yigang; Cheung, Fan; Wang, Xuanbin; Zhang, Zhangjin; Feng, Yibin
Aim of Study . Gegen Qinlian decoction (GQLD) is an ancient Chinese medicine formula for treating diseases with inner heat. The aim of this study is to investigate the antitumor effect of GQLD in human renal carcinoma cell (RCC) and its possible mechanism. Method . High-performance liquid chromatography was used to identify and quantify active compounds in GQLD. Inhibition of tumor growth was determined by xenograft model. Cell viability on treatment with the decoction was determined by MTT assay; quantitative real-time polymerase chain reaction and immunoblotting were used to determine gene and protein expression; matrix metalloproteinase-2 (MMP-2) activity was detected by gelatin zymography and in vitro enzymatic reaction assay. Results . Thirteen major peaks were detected in the decoction, 8 of which were identified as berberine, baicalin and baicalein, pueranin, daizidin, liquiritin, wogonoside, and wogonin. GQLD exhibited potent inhibition on xenografted expansion of RCC cells. Interestingly, GQLD treatment did not induce cell death to RCC cells, but blocked the neoangiogenesis in xenografted RCC tumor. Particularly, we found that GQLD significantly inhibited MMP-2 in RCC cells, which was involved as a critical factor in avascular growth of RCC. GQLD directly suppressed the enzyme activity of MMP-2. Radix Scutellariae was the major herbal component that contributed to the potent inhibition of MMP-2. Conclusion . The findings of this study provide experimental evidence of the inhibition of expansion and neoangiogenesis of renal carcinoma by Chinese medicine formula GQLD with involvement of MMP-2 suppression.